Alterations in the health state on the first week of life in newborn from adolescent mothers - Torres, Daniele Araújo; Cardoso, Maria Vera Lúcia Moreira Leitão; Silva, Grazielle Roberta Freitas da; Lúcio, Ingrid Martins Leite (Rev Rene, 2006)
This is a descriptive, documentary as well a quantitative study whose aim was to identify the alterations in the health therapeutic state of life in the newborn (NB in the first week of life), child of adolescent mother. It was conducted in a neonatal unit of a reference maternity ward, in Fortaleza – Ceará during the months of September and October; 2004.We used as a sample the story of 32 NB children of adolescent mothers, with the permission of their own mothers. The data referred to the story of the birth and the admittance into hospital, on the first week of life aiming at the health state, extracted from the NB’s medical chart. We concluded that 16(50%) of the NB were premature. Such a fact can bring a number of alterations in the NB’s health state due to the immaturity of its physiological systems. The most frequent diagnostic impression was the Respiratory Distress Syndrome (38, 9%). Most of the babies diet was mother’s milk which they received through orogastric tubes (68,8%).Among the therapeutics the most highlighted ones were the oxygen therapy for acrylic helmet (48,1%), the phototherapy (88,9%) and antibiotic therapy (32,3%).